ENGLISH TEACHERS' PERCEPTIONS OF THE USE OF TECHNOLOGY IN A RURAL AREA IN INDONESIA - Bulan, Arif; Hasan, Hasan; Srirahmawati, Ija (Annual International Conferences on Language, Literature, and Media, 2023)
English teachers' perceptions of the use of technology such as interactive multimedia for learning and differentiated learning are important to know, considering that they are part of the Kurikulum Merdeka (Indonesia’s most recent curriculum in all education). This case study aims to explore English teachers' perceptions of interactive multimedia for learning and to unearth English teachers' perceptions of differentiated learning in a rural area in Indonesia. This case study utilizes 22 junior high school English teachers as the respondents of the interview. The results of this study show that (1) some teachers have not developed any interactive multimedia for learning, (2) some other teachers have not participated in any trainings or workshops on making interactive multimedia for learning, (3) some other teachers have not made any materials based on differentiated learning principles, and (4) some other teachers have not participated in any trainings on making differentiated learning materials. These teachers thus perceived that there is a need for training or workshops on making interactive multimedia for learning and differentiated learning for junior high school English teachers in the district organized by the local ministry of education office, the teachers’ forum, and higher education institutions (colleges/universities). Based on the results of this study, it is suggested that there are probably many similar cases in rural areas in Indonesia where the teachers are struggling with modern technology while the curriculum encourages them to use modern technology in the teaching and learning process.